A implantação do “Currículo da Cidade” na visão do docente: impressões e dificuldades iniciais - Aparecido, Paulo Henrique [UNIFESP] (2020)
This work aimed to analyse the vision of teachers regarding the implementation of the new curriculum base in the city of São Paulo in 2018, to the Elementary School II, referring to the Natural Sciences curriculum component and reflect on possible difficulties encountered by teachers in this process. At the end of 2017, a new school curriculum was presented in the city of São Paulo for Primary Education, the "Currículo da Cidade", with a proposal to align the curriculum guidelines of the Municipality of São Paulo with the process of building the Common National Curriculum Base, a document that defines the essential learning to which all Brazilian students are entitled throughout Basic Education. Faced with this scenario, the following research problems were raised: What is the teachers' perception of the implementation of this new curriculum? Are the teachers getting adequate support for the training courses to work with the new curriculum? How will the subjects be continued in this transposition? What about the updating of teaching material? To try to answer these questions, it was tried with this qualitative research to make an analysis of the models of training of science teachers, whose search for a critical-reflexive profile is desirable to gain autonomy for the construction and/or implementation of curriculum during their professional activity. First, a theoretical survey was made on the definition of curriculum, passing by authors such as Sacristán, Saviani, Macedo and Lopes and a brief historical survey on the BNCC and the reorganization of elementary education in the São Paulo Municipal Education Network in recent years. This sought to base this research considering the profile of the teachers interviewed and considering extremely relevant the vision of the teacher about the implementation of the “Currículo da Cidade”, not being seen as a mere executor, but as an important, critical and participative character in decisions that affect the environment and school community.